2012
DOI: 10.2174/092986712803833218
|View full text |Cite
|
Sign up to set email alerts
|

Non-Viral Engineering of Skin Precursor-Derived Schwann Cells for Enhanced NT-3 Production in Adherent and Microcarrier Culture

Abstract: Genetic engineering of stem cells and their derivatives has the potential to enhance their regenerative capabilities. Here, dendrimer- and lipofection-based approaches were used for non-viral neurotrophin-3 (NT-3) over-expression in Schwann cells differentiated from skin precursors (SKP-SCs). A variety of dendrimers were first tested for transfection efficiency on HEK 293T cells, with PAMAMNH2 G4 found most effective and used subsequently for SKP-SCs transfection. Plasmid-based expression resulted in increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…[12][13][14] Recent studies have revealed that delivery of SCs to NCs is advantageous for nerve repair, particularly when using SCs that overexpress an NF, such as basic fibroblast growth factor (FGF-2), 15,16 glial cell line-derived neurotrophic factor (GDNF), 17,18 nerve growth factor (NGF), 19 brainderived neurotrophic factor (BDNF), 20 or neurotrophin-3 (NT-3). 21 However, an increasing number of studies have indicated that the application of multiple NFs, rather than a single type, holds greater therapeutic promise. 4,22,23 If we can modify a cell to upregulate multiple NFs, nerve regeneration and functional recovery might be greatly enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Recent studies have revealed that delivery of SCs to NCs is advantageous for nerve repair, particularly when using SCs that overexpress an NF, such as basic fibroblast growth factor (FGF-2), 15,16 glial cell line-derived neurotrophic factor (GDNF), 17,18 nerve growth factor (NGF), 19 brainderived neurotrophic factor (BDNF), 20 or neurotrophin-3 (NT-3). 21 However, an increasing number of studies have indicated that the application of multiple NFs, rather than a single type, holds greater therapeutic promise. 4,22,23 If we can modify a cell to upregulate multiple NFs, nerve regeneration and functional recovery might be greatly enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy is a relatively recent approach to study the regenerative effects of overexpression of specific therapeutic proteins on the injured nerve. The introduction of genetically engineered glia cells overexpressing trophic and tropic factors in nerve guides may improve their proregenerative properties and guides filled with genetically modified cells more closely resemble the autograft (Eggers et al, ; Godinho et al, ; Gravvanis et al, ; Hu et al, ; Kokai et al, ; Li et al, ; May et al, ; Santosa et al, ; Shakhbazau et al, , b; Yu et al, ). Adenoviruses were the first viral vectors used to successfully transduce Schwann cells in a peripheral nerve (Dijkhuizen et al, ; Shy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate cell adherence to microcarriers, cell/microcarrier suspensions were agitated intermittently for 3 min every half an hour for 5 h (Alfred et al, ) and continued in static or stirred culture. In this study, “Static Microcarrier culture” refers to SKP‐SCs‐seeded microcarriers cultured without stirring, whereas “Stirred Microcarrier culture” refers to cells cultured on microcarriers in a custom mini‐stirred culture model (vessel 50 mL size) with 10.0 mL SC medium described earlier (Shakhbazau et al, ) (5 × 10 4 cells/mL, 7400 cells/cm 2 on Cytodex 3 carriers) that was agitated at 60 rpm (Stirred Microcarrier). Cells were also cultured in dynamic culture in 100.0 mL SC medium in a stirred suspension bioreactor (Stirred Microcarrier, Bioreactor) (NDS Technologies, Inc., Vineland, NJ, nominal volume 125 mL).…”
Section: Methodsmentioning
confidence: 99%